Analysis of the Influence of Advertising Creativity, Product Campaigns, and Brand Ambassador Credibility on Customer Loyalty for The Wearing Klamby Brand - Andina Tazkiya Nurlibna; Clarisa Izdiharjati; Muhammad Givari Arnanda; Muhammad Aras; La Mani (UniSadhuGuna Business School, 2024)
A good marketing communication strategy greatly affects a brand’s customer loyalty, especially when a brand can consistently create a creative and engaging marketing communication strategy to promote their brand and products. This is in line with a brand's ability to create creative advertisements, develop engaging product campaigns, and choose brand ambassadors with good credibility. Therefore, this study aims to know how advertising creativity, product campaigns and brand ambassador credibility affect Wearing Klamby’s customer loyalty. Distributed online Google form questionnaires to 100 audiences who are active on social media, have seen advertisements or campaign content for Wearing Klamby products, are familiar with the brand ambassador for Wearing Klamby, and have previously purchased Wearing Klamby products. All respondents are women who lived in Indonesia and were classified as the middle to upper economic class. After all of the data were collected, they were processed using measurement model evaluation and structural model evaluation. Creative advertisements, engaging product campaigns, and brand ambassadors with good credibility had a significant influence on the level of customer loyalty to a brand. This research found that customer loyalty is significantly influenced by the creativity of advertisements, product campaigns, and the credibility of brand ambassadors.